Faktor-Faktor yang Berhubungan Dengan Lama Hari Rawat Pasien BPJS Kesehatan di Rumah Sakit Mardi Waluyo Kota Metro - Atmojo, Catur Yuli; Elasari, Yunina; Surmiasih, Surmiasih; Nugroho, Tri Adi (Journal of Nursing Invention, 2024)
Background: Length of hospitalization is indicator accomplishment of patient care in hospital. Long hospitalization causes increased treatment costs, whereas hospitalization that is too short will increase the risk of patient re-admission. The majority of inpatients in Indonesia are Health patients of social insurance administration organization with a payment system based on the ina-cbgs claim package which seeks to shorten patient treatment time to avoid economic losses so that the Length of hospitalization value is still below 6-9 days. Objective: The research to determine the correlation between sociodemographic factors and length of stay for health patients of social insurance administration organization in Mardi Waluyo Hospital at Metro City. Method: This observational analysis study was designed to collect data retrospectively using a cross-sectional design. are all Health participants of social insurance administration organization who will be treated at Mardi Waluyo Hospital in Metro City 2022, with a total of 13.903 patients. The sampling technique used total sampling. Data were analyzed used the Chi Square test Result: The results of the analysis show that there is a significant correlation between (age p= <0.001); (gender p=<0.001); (treatment class p= 0.001), (type of disease p= 0.001); and (number of disease diagnoses p=<0.001) with length of stay. Conclusion: It is recommended that research sites conduct a more in-depth analysis of factors related to length of hospitalization so that the services provided to patients are more effective and efficient and can increase patient satisfaction.